The role of chromatin remodeling in medulloblastoma - Jones, David T. W.; Northcott, Paul A.; Kool, Marcel; Pfister, Stefan (Brain pathology, 2013)
The unexpectedly high frequency and universality of alterations to the chromatin machinery is one of the most striking themes emerging from the current deluge of cancer genomics data. Medulloblastoma (MB), a malignant pediatric brain tumor, is no exception to this trend, with a wealth of recent studies indicating multiple alterations at all levels of chromatin processing. MB is typically now regarded as being composed of four major molecular entities (WNT, SHH, Group 3 and Group 4), which vary in their clinical and biological characteristics. Similarities and differences across these subgroups are also reflected in the specific chromatin modifiers that are found to be altered in each group, and each new cancer genome sequence or microarray profile is adding to this important knowledge base. These data are fundamentally changing our understanding of tumor developmental pathways, not just for MB but also for cancer as a whole. They also provide a new class of targets for the development of rational, personalized therapeutic approaches. The mechanisms by which these chromatin remodelers are dysregulated in MB, and the consequences both for future basic research and for translation to the clinic, will be examined here.
Gesehen am 09.04.2021
Mini-symposium: When genetics meets epigenetics - a new option for therapeutic intervention in brain tumors?